Crosstalk between plant responses to pathogens and herbivores a view from the outside in - Taylor, Jane E (Journal of experimental botany, 2004)
Plants encounter numerous pests and pathogens in the natural environment. An appropriate response to attack by such organisms can lead to tolerance or resistance mechanisms that enable the plant to survive. Many studies concentrate on the signalling pathways that enable plants to recognize and respond to attack, and measure the downstream effect in either biochemical or molecular terms. At the whole plant level, ecologists examine the fitness costs of attack not only for the plant but also over a range of trophic levels. The links between these differing levels of study are beginning to be addressed by the adoption of molecular approaches in more ecologically relevant settings. This review will describe the different approaches used by ecologists and cell biologists in this field and will try to address the question of how we can explore the response to, and consequences, of attack by multiple enemies